Comparison of the Observed Rainfall with Rainfall Estimated by CLIGEN Climate Model in terms of Drought Analysis - Müberra Erdoğan; Kadri Yürekli; Mehmet Murat Cömert (Turkish Journal of Agriculture: Food Science and Technology)
Standardized Precipitation Index (SPI) is used to determine dry and humid periods according to the cumulative probability method at different time scales. . In this study, the rainfall data between the years of 1980-2018 belonging to of Kayseri Meteorology Station was simulated by CLIGEN stochastic climatic data generator. SPI indices calculated by using observed and simulated precipitation were evaluated with the statistical methods at the time scales of 3-, 6-, 9- and 12- months. The SPI values of 3-, 6-, 9- and 12- month which are observed and simulated with CLIGEN are close to each other and the performance of the model is very high in calculating the SPI values of these time series. However, as the time period increased, the model's representative ability decreased.